2018
DOI: 10.1111/obr.12812
|View full text |Cite
|
Sign up to set email alerts
|

The effect of screen advertising on children's dietary intake: A systematic review and meta‐analysis

Abstract: Summary Evidence indicates that screen advertising for unhealthy food results in significant increases in dietary intake among children. This review was undertaken with the main aim of estimating the quantitative effect of screen advertising in experimental and nonexperimental conditions on children's dietary intake. Systematic searches were undertaken of interdisciplinary databases. Studies from 1980 to April 2018, all geography and languages, were included; participants were children and adolescents aged bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 57 publications
11
126
2
7
Order By: Relevance
“…We found that kindergarten children not meeting the screen time guideline were three times more likely to be overweight or obesity than those meeting the guideline. This is supported by evidence in children and adolescences, which suggests that excessive screen media exposure is associated with increased eating while viewing screens as well as reduced sleep duration; and these, in turn, could lead to higher adiposity [43]. However, our result did not align with findings in high-income countries, which suggest no associations between screen guidelines compliance and adiposity in preschool-aged children and toddlers [23,24,26,44].…”
Section: Discussioncontrasting
confidence: 56%
“…We found that kindergarten children not meeting the screen time guideline were three times more likely to be overweight or obesity than those meeting the guideline. This is supported by evidence in children and adolescences, which suggests that excessive screen media exposure is associated with increased eating while viewing screens as well as reduced sleep duration; and these, in turn, could lead to higher adiposity [43]. However, our result did not align with findings in high-income countries, which suggest no associations between screen guidelines compliance and adiposity in preschool-aged children and toddlers [23,24,26,44].…”
Section: Discussioncontrasting
confidence: 56%
“…Most recently, a study found a 25% increase in fast food advertising between 2011 and 2016 across 31 stations broadcasted in Toronto, Canada's largest broadcast market [56]. Fast food advertisements have previously been associated with an increase in fast food consumption, and an increased risk of obesity in children [21,[57][58][59][60]. Specifically, studies have found children preferred foods when they thought foods were from familiar fast food brands (e.g., McDonald's) [61,62].…”
Section: Fast Food Advertisingmentioning
confidence: 99%
“…Physical aspects of mealtime environment have been explored most in relation to mealtime television use, linked to child overweight in a recent metaanalysis [10]. Possible mechanisms include exposure to obesogenic food advertising (which can have both immediate effects on dietary intake, and longer term effects on fast food preferences [11,12]); adverse effects of mealtime screen use on appetite regulation and control [13]; and less parental monitoring of food consumption [14]. The social and physical context of mealtimes may have independent and/or interactive effects on children's diet, although it is not clear whether mealtime screen use compromises or promotes a positive atmosphere [15,16].…”
Section: Family Mealtime Environmentmentioning
confidence: 99%